Plasma-Treated Flammulina velutipes-Derived Extract Showed Anticancer Potential in Human Breast Cancer Cells - Sarmistha Mitra; Pradeep Bhartiya; Neha Kaushik; Linh Nhat Nguyen; Rizwan Wahab; Sander Bekeschus; Eun Ha Choi; Nagendra Kumar Kaushik (Applied Sciences, 2020)
Natural products with medicinal properties are among alternative therapies of interest due to their high body tolerance. We aimed to determine whether nonthermal gas plasma could enhance the medicinal value of Flammulina velutipes mushrooms. Generated gas plasma was characterized by its emission spectrum in ambient air, pH, temperature, and H2O2 and NOx concentrations after exposure for various periods. Phenolic and flavonoid contents in the extracts were measured using antioxidant assays and Fourier transform infrared and ultraviolet-visible spectroscopy. We analyzed the effects of the plasma-treated mushroom-derived extracts against breast carcinoma using the MCF7 and MDA-MB231 cell lines. The extracts significantly and concentration dependently inhibited the growth of breast cancer cells without inducing toxicity in normal MCF10A cells, and induced apoptosis via oxidative stress, evidenced by DNA damage (γ-H2AX foci formation), and increased the population of MCF7 breast cancer cells arrested in the G2/M phase of the cell cycle. The extracts also induced mitochondrion-mediated apoptosis of MCF7 cells through cytochrome c release and caspase cleavage activity. The plasma improved the biological activity of mushrooms by increasing their phenolic compounds that prevented the growth of breast cancer cells in vitro.